PD-L1 expression and tumor mutational burden are independent biomarkers in most cancers - Yarchoan, Mark; Albacker, Lee A.; Hopkins, Alexander C.; Montesion, Meagan; Murugesan, Karthikeyan; Vithayathil, Teena T.; Zaidi, Neeha; Azad, Nilofer S.; Laheru, Daniel A.; Frampton, Garrett M.; Jaffee, Elizabeth M. (JCI insight, 2019)
PD-L1 expression and tumor mutational burden (TMB) have emerged as important biomarkers of response to immune checkpoint inhibitor (ICI) therapy. These biomarkers have each succeeded and failed in predicting responders for different cancer types. We sought to describe the PD-L1 expression landscape across the spectrum of ICI-responsive human cancers, and to determine the relationship between PD-L1 expression, TMB, and response rates to ICIs. We assessed 9887 clinical samples for PD-L1 expression and TMB. PD-L1 expression and TMB are not significantly correlated within most cancer subtypes, and they show only a marginal association at the tumor sample level (Pearson's correlation 0.084). Across distinct tumor types, PD-L1 expression and TMB have nonoverlapping effects on the response rate to PD-1/PD-L1 inhibitors and can broadly be used to categorize the immunologic subtypes of cancer. Our results indicate that PD-L1 expression and TMB may each inform the use of ICIs, point to different mechanisms by which PD-L1 expression regulates ICI responsiveness, and identify new opportunities for therapeutic development. Funding was provided by Foundation Medicine Inc., the Johns Hopkins Bloomberg-Kimmel Institute for Cancer Immunotherapy, the Viragh Foundation, the National Cancer Institute Specialized Program of Research Excellence (SPORE) in Gastrointestinal Cancers (P50 CA062924), the NIH Center Core Grant (P30 CA006973), the Norman & Ruth Rales Foundation, and the Conquer Cancer Foundation.